Leaving time : a novel - Picoult, Jodi, 1966- (New York : Ballantine Books, 2014)
"Alice Metcalf was a devoted mother, loving wife, and accomplished scientist who studied grief among elephants. Yet it's been a decade since she disappeared under mysterious circumstances, leaving behind her small daughter, husband, and the animals to which she devoted her life. All signs point to abandonment . . . or worse. Still Jenna--now thirteen years old and truly orphaned by a father maddened by grief--steadfastly refuses to believe in her mother's desertion. So she decides to approach the two people who might still be able to help her find Alice: a disgraced psychic named Serenity Jones, and Virgil Stanhope, the cynical detective who first investigated her mother's disappearance and the death of one of her mother's co-workers. Together these three lonely souls will discover truths destined to forever change their lives. Deeply moving and suspenseful, Leaving Time is a radiant exploration of the enduring love between mothers and daughters"--
Keywords: Teenage girls -- Fiction; Mothers and daughters -- Fiction; Missing persons -- Fiction; FICTION / Contemporary Women; Mystery fiction; Suspense fiction